Microevolutionary relationships between biotypes of Elymus confusus, E. peschkovae, and E. sibiricus (Poaceae) according to hybridization and sequencing of the nuclear gene GBSS1 (waxy) - Agafonov Alexander V. (EDP Sciences, 2021)
According to descriptions, the Siberian species E. peschkovae and E. confusus differ in the presence or absence of trichomes on lemma and rachilla surfaces only. Two methods were used for study microevolutionary relationships between these species: hybridization of biotypes from different locations and analysis of nucleotide sequences of the low-copy nuclear gene GBSS1. Created and grown hybrids in combinations AMU-8804 × BER-0807 and AMU-8804 × BUK-1109 showed complete seed sterility in two field vegetations. Taking into account wide species areas, 3 hybrids were created between Magadan biotypes from a common habitat in the combination E. confusus MOL1887 × E. peschkovae MOL-1882. The plants showed seed fertility (SF) of 0–3 %. This result does not obscure the possibility to assess SF in the F2 generation and the character of inheritance of diagnostic traits. A comparative study of the GBSS1 gene sequences in accessions was carried out in comparison with clones of reference species. Differentiation of clones by the St2 subgenome in E. confusus, E. peschkovae, E. sibiricus and E. caninus did not reveal a clear relationships between the species. Meanwhile, a certain species specificity for the H1 subgenome was noted, confirming the existence of microevolutionary isolation of these species.